Rancang Bangun Aplikasi Sentra Pelayanan Kepolisian Terpadu Berbasis Web Pada Polres Badung - Galuh Candra Wardani; Henry Bambang Setyawan; A. B. Tjandrarini (Fakultas Ilmu Komputer dan Desain - Unsurya, 2023)
The Integrated Police Service Center or often abbreviated as SPKT is a part of the police to provide services to the community, in the form of receiving and first handling reports or complaints. So far, the reporting process carried out by the community is still done manually, by coming directly to the SPKT Polres Badung so it’s a hassle for the community and the storage of physical documents from various incoming reports continues to grow so it requires a lot of space. So in this study a web-based application was built that could make it easier for the public to report and help SPKT Polres Badung to cut down the storage space for physical reporting documents. This application uses the Software Development Life Cycle (SDLC) method with a waterfall model which consists of the processes of communication, planning, modeling, construction, and deployment. Based on the results of the trial and evaluation of the system for the application built, it can be concluded that this application can help the public report online and assist the SPKT Polres Badung administrator in managing reporting and storing reporting documents digitally.